Major import markets for wooden household furniture - International Trade Centre UNCTAD/GATT. (Geneva : International Trade Centre UNCTAD / GATT, 1982)
The book discusses overall world trade trends, market characteristics; gives marketing recommendations; and for each country gives comments and data on basic demand factors, production, foreign trade, consumption, distribution network, price levels, trade practices, styles of furniture, transport factors, packaging, advertising, promotion, trade fairs, local industry structure, major enterprises, raw materials, technology, quality standards; and lists trade associations, purchasing groups and other useful addresses.
Spine title: Wooden household furniture.
Errata slip inserted.
Includes bibliographical references.
II 15/01/2019
Loans
Keywords: Furniture industry and trade; Market surveys